The tip of the iceberg: Profiling cooling agents using computational approaches to inform tobacco regulatory science - Saibal Chakraborty; P. Dilip Venugopal; Maria Kaltcheva; Jueichuan Connie Kang; Reema Goel (PLoS ONE, 2026)
Cooling agents (chemicals added to impart a cooling sensation) in tobacco products are receiving increased attention due to their use as menthol substitutes. However, detailed information on their chemical structures, physico-chemical properties, cooling activity, and human and ecotoxicity potential has not been compiled. Our goal was to profile cooling agents that could be used as menthol substitutes in tobacco products, along with descriptions of their cooling properties and estimated toxicological effects. First, we compiled a library of 228 cooling agents, including 180 unique two-dimensional (2-D) chemical structures based on a review of multiple public data sources (literature, invention patents, and public databases). The library includes chemicals with a “cool” and/or “mint” flavor profile as designated by the Flavor and Extract Manufacturers Association (FEMA), chemicals reported to activate the cation channel transient receptor potential melastatin 8 (TRPM8) receptor, and/or chemicals with reported subjective perceived sensory cooling. Second, we classified the cooling agents into three main chemical skeletons using similar structural motifs and estimated their physico-chemical properties related to cooling attributes using Schrödinger Canvas software, including log octanol-water partition coefficient (LogKow), vapor pressure, and electrotopological state index. Third, to investigate the cooling agents’ similarity to each other and to menthol, we applied an unsupervised machine learning algorithm (Knowledge Discovery by Accuracy Maximization [KODAMA]) and hierarchical clustering techniques and identified six clusters. Fourth, we compiled available perceived cooling intensity data. Fifth, we used models based on experimental and predicted data (EPA’s web-based Hazard Comparison Module [HCM]) to estimate human health toxicity and ecotoxicity. Some cooling agents are associated with genotoxicity, developmental toxicity, skin irritation, and eye irritation, and pose toxicity to fish, algae, and invertebrates. Using this surveillance approach will help inform future tobacco regulatory decisions and policies by profiling chemicals used as cooling agents in tobacco products and those that pose potential health hazard concerns.